[Cost-Effectiveness Analysis of Maribavir in Patients with Post-Transplant Cytomegalovirus Infection or Disease that are Refractory or Resistant to Conventional Therapy] - Marcellusi, Andrea; Bini, Chiara; Corinti, Simone; Fioravanti, Laura; Dalla Vedova, Laura; Amorosi, Stacey L.; De Lacey, Tam; Chowdhury, Emtiyaz; Mennini, Francesco Saverio (Farmeconomia. Health Economics and Therapeutic Pathways, 2023)
OBJECTIVES: Cytomegalovirus (CMV) infection represents a serious post-transplantation complication, particularly among transplant recipients with resistant or refractory (R/R) infection. Despite the improvement made in CMV prevention and treatment, remains a need for new therapies that are better tolerated and safer for patients, especially for refractory or resistant (R/R) infections. This analysis investigates the cost-effectiveness of maribavir versus investigator-assigned therapy (IAT) for treatment of post-transplant R/R CMV in the Italian context. METHODS: The analysis was conducted from the National Health Service (NHS) perspective using a Markov model previously developed in Excel® to evaluate the cost-effectiveness of maribavir versus IAT for the treatment of post-transplant R/R CMV. Health event rates and transition probabilities were informed by data from observational studies and from SOLSTICE clinical trial, which compared maribavir to conventional antiviral treatments for transplant patients with R/R CMV infections. Utilities were from SOLSTICE and a utility vignette study. Costs inputs were derived from published literature and Italian national tariffs for outpatient and hospital services. Costs and outcomes were discounted by 3%. RESULTS: Maribavir compared to the IAT used for the treatment of post-transplant R/R CMV achieved an incremental cost of € 11,455 for an incremental quality adjusted life year (QALY) gain of 0.313. This resulted in an incremental cost-effectiveness ratio of € 36,626/QALY, for maribavir compared to IAT, which is below the generally accepted, national willingness-to-pay threshold for orphan drugs (€ 37,000/QALY). CONCLUSIONS: This analysis showed that maribavir, an orphan drug treatment, is cost-effective compared to the current antiviral treatments used for treatment of post-transplant R/R CMV.